Reports on Ongoing and Past Research Project The Dictionaries of the Local Languages of Banten - Ade Jaya Suryani (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2015)
Reports on Ongoing and Past Research ProjectThe Dictionaries of the Local Languages of Banten